Estudo do Cultivo de dois clones de Escherichia coli recombinantes (eIF, LACK) para a Expressão de Antígenos da Leishmania chagasi - Vaz, Michelle Rossana Ferreira (2008)
With advent of the technology of the recombinant DNA, the recombinant protein expression becomes an important tool in the studies of the structure, function and identification of new proteins, mainly with therapeutical purposes. The Escherichia coli has been procarioto predominant in the studies of genetic engineering due to wealth of information regarding its metabolism. Despite the expressivo advance of the studies of molecular biology and the immunology of the infections, it does not exist, currently, no prophylactic drug capable to prevent calazar. Of this form, it exists a great necessity of specific antigen identification for the vaccine development and kits for disgnostic against the visceral Leishmaniose. In this context, this work objectified to study the recombinant antigen expression of the Leishmania chagasi during the culture of Escherichia coli in shaker. A first set of assays was carried through with the objective of if knowing the kinetic behavior of the growth of two clones recombinant proteins (eIF, LACK) in two different compositions of culture medium (2xTY, TB) supplemented by antibiotics, without IPTG addition. In the second stage of the assays, the procedure of induction for IPTG was carried through, in order to verify the influence of the composition of the ways tested in the expression them recombinant proteins. On the basis of the gotten results, can be observed that the high complexity of culture medium favored the kinetic one of growth of clones recombinant (eIF, LACK), however, to if to deal with the assays submitted to the procedure of induction for IPTG, the raised complexity of culture medium did not favor the expression of recombinant proteins. On the other hand, they had been gotten resulted positive for all clones recombinant (eIF, LACK) tested, confirmed through the eletroforético profile